Student satisfaction with a complementary service: a perception study in a Public Higher Education Institution in Ecuador (Revista Electrónica Calidad en la Educación Superior, 2024)
This study addresses the perceived value of the student service generated by the Student Welfare Unit (SWU) at a public higher education institution (HEI) in Ecuador. Interviews were conducted with the SWU to establish the service process of eight programs offered. The type of study is mixed-approach, with a non-experimental design of cross-section and correlational scope. The satisfaction level was evaluated through 710 student surveys, and the experienced issues were defined and categorized from both perspectives based on the HEI's value chain. It is concluded that, despite students may or may not experience issues within the service, they may or may not be satisfied. Essentially, the perception of quality of the complementary student service provided by the SWU is not necessarily related to student satisfaction.
Keywords: student welfare; quality perception; student Satisfaction; complementary Student Service